Microbial Contamination in Airplane Cabins:Health Effects and Remediation - Menzies, Dick (Air Quality in Airplane Cabins and Similar Enclosed Spaces, 2005)
Microorganisms that affect human health are found in all indoor environments, including cabins of commercial aircraft. Those that arise from human sources can be transmitted by direct contact, droplets, or the airborne route. Infections from human sources include Influenza, Rhinovirus, SARS and tuberculosis. Transmission by the airborne route can be reduced by sterilizing the air with ultraviolet germicidal irradiation, or by diluting the contaminated air with outdoor air through ventilation. Microbes arising from environmental sources include bacteria, fungi and other organisms such as protozoa. These usually have very simple requirements for growth – water and a simple substrate such as dust. They cause health effects through direct infection rarely (one example is Legionnella), but more commonly cause immune reactions resulting in hypersensitivity or allergy mediated diseases. Environmental sources of microbial contamination are best prevented, but can be remediated through cleaning, germicidal chemicals, or ultraviolet germicidal irradiation. Airborne microbial substances including toxins, antigens and viable organisms can be removed by outdoor air ventilation or filtration. In aircraft cabins transmission of pathogens from human sources is difficult to control, but airborne transmission can be reduced through increased outdoor air ventilation or filtration. Environmental microbial contamination can, and does occur in aircraft cabins. These microbial sources are best prevented but, if detected, can be removed through cleaning or disinfection. Ultraviolet germicidal irradiation is an under-utilized technology that may be useful for sterilizing air as well as potential environmental sources.